Govorne ploskve Simone Semenič kot performativno razgaljanje jezika - Pori, Eva (Amfiteater (Ljubljana), 2019)
With her distinctive authorial (no longer) dramatic writing and her performance art pieces derived from this writing, Simona Semenič has brought onto the Slovenian scene a radical de(con)struction of the dramatic form, which also manifests itself in a demolition of conventional linguistic patterns and concepts. This article examines and analyses the linguistic destabilisations of the texts of Simona Semenič by applying to them three different aspects heretofore untested on her opus: R. Jakobson's theory of the sign, M. Heidegger's hermeneutic philosophical thought, and V. Novarina's theory of theatre. The changed nature of the dramatic form, which appears on several language planes, will be examined with the help of particular examples: a passage from the metatheatrical text seven cooks, four soldiers, three sophias (2014) and Semenič's other plays, for example, the monodrama or documentary performance piece i, the victim (2007), the feast (2010) (the author as narrator), the epically rendered work 1981 (2013) or the mediated text 5boys.si (2008) (the dramatic character as director or commentator of the action). The fundamental language-speech elements that Semenič plays through are: the flow of the text through different linguistic varieties (general colloquial language, regional (Ljubljanian) colloquial language, littoral (subNanos) dialect, spam language - English), the language is spurtive, often suffused with slang, vulgarities and foreign words, lower colloquial terms and pejoratives, it is written without punctuation and capitals, the syntax is eroded, simplified and distinctively fragmentary (short, clipped, occasionally disconnected sentences), the stage directions pass into dialogue and take up a metalinguistic function. A short oriented review of the texts of Simona Semenič, focusing on an analysis of language-speech aesthetics, shows that Semenič generates a theatre of a higher language plane and consciousness, a theatre of un-veiling the otherwise veiled vocal dimension of language or of the sonic parameters of the word, or, in Artaud's words, a theatre of unveiling the otherwise veiled metaphysical plane of language. In her projects, she introduces a particular aspect of speech, based on an apparent incomprehensibility of the sayable and the alogia or nonsensicalness of the said. In novarinaesque spirit, she perforates and illuminates the text, so that language as a natural phenomenon may unveil itself. She returns language to the space, she unbinds it, she frees it and she shows that it is not only syntax that holds it together. In her texts, she in fact writes down what the texts are missing, i.e., the unsayable; she names the unnameable, thus reminding us of an essential idea: a text is not made just out of words. In the search for new aesthetic conceptions, for a fusion of diverse staging methods and for polyphonic speech surfaceness, Semenič begets fresh ideas and approaches by means of which she enacts a movement from the static to the dynamic. She no longer relies on consciousness and the word, but rather searches for her origin in the unknown, the unconscious, the unwritable and the unsayable - in voice, movement, ringing, sound, even silence. The sound of words, the meaning of form, the unspoken word, the ringing of silence (Heidegger), the mute body onstage are empowered, becoming independent expressive media and speaking (out) for themselves, each in its own particular dialect. By passing from the meaning to the sound of words, from rigid language to language in movement, she creates a particular stage language, which is no longer an expression of literature, but of theatre itself. By joining the conscious with the unconscious, the visible with the invisible, with the metamorphoses of bodies and voices, by a deviation from traditionalism and by a transition into a phase of searching for the primal, she fashions an original image, an image of a living speech made of voices and bodies; she unveils herself and speaks from her depth. Semenič is thus concerned with a different vision and naming of the world. Her action is an expression of the capacity to see things from other viewpoints and of the overcoming of linguistic norms and of language-speech forms of enunciation belonging to traditional theatre. By developing a new aesthetics and a particular acting or dramatic language she brings to light the particular value and form of performance texts. Deriving from Jakobson's theory of the sign, Heidegger's hermeneutic philosophical thought about language, supplemented by Novarina's theory of theatre as a language or as all-encompassing speech, Semenič, on a linguistic level, hearkens to words and unveils, in an apparent alogia of changes of sound (of voice and body), a plane of language otherwise metaphysical. All of the language-speech elements that she displaces and plays through, pass onto the signifying plane, gain autonomous value and thus become conveyors of sense and carriers of meaning. By interweaving elements of language-speech alogia, nonsensicalness, hybridity and fragmentariness, which pass onto the signifying plane, Semenič establishes a language of dramatic contrasts and thus demonstrates that today's textuality is of a special nature. It is based upon a concept of nonlinear structuring of (no longer) dramatic 78 speech surfaces of diverse, often mediated discourses, while in a "dramatized society" (R. Williams), drama or text have become a scene of dynamic transitions and overlaps of epistemologies coming from various media and literary and performance tactics (T. Toporišič).
Keywords: acting speech; Heidegger, Martin; igralski govor; Jakobson, Roman; jezik; language; Novarina, Valere; performativity; performativnost; Semenič, Simona